Excited state and charge-carrier dynamics in perovskite solar cell materials. (28th January 2016) - Ponseca, Carlito S; Tian, Yuxi; Sundström, Villy; Scheblykin, Ivan G
Abstract: Organo-metal halide perovskites (OMHPs) have attracted enormous interest in recent years as materials for application in optoelectronics and solar energy conversion. These hybrid semiconductors seem to have the potential to challenge traditional silicon technology. In this review we will give an account of the recent development in the understanding of the fundamental light-induced processes in OMHPs from charge-photo generation, migration of charge carries through the materials and finally their recombination. Our and other literature reports on time-resolved conductivity, transient absorption and photoluminescence properties are used to paint a picture of how we currently see the fundamental excited state and charge-carrier dynamics. We will also show that there is still no fully coherent picture of the processes in OMHPs and we will indicate the problems to be solved by future research.